ANALISIS KINERJA SATUAN POLISI PAMONG PRAJA KABUPATEN BUOL - R. Dunggio, Runi Rizkiana (STISIPOL Mujahidin Buol, 2023)
This research aims to determine the performance of the Buol Regency Civil Service Police Unit. The research method used is a descriptive qualitative research method. The location of the research was carried out at the Buol Regency Civil Service Police Unit Office. The time for carrying out the research was carried out for two months, namely from November to September 2023. The data collection techniques used were Observation, Interview Guide, Documentation, in the research Qualitative Descriptive Data reduction, Data presentation, and Final stage. The research results show that the performance of employees at the Public Security Bureau at Satpol PP is good, this can be seen from good work behavior, loyalty, and commitment to good work practices. It also emphasizes the importance of creativity, innovation, and regulatory compliance, as well as the importance of solving problems and ensuring good work behavior.